Metal Complexes in Target-Specific Anticancer Therapy: Recent Trends and Challenges - Gemechu Shumi; Tegene Desalegn; Taye B. Demissie; Venkatesha Perumal Ramachandran; Rajalakshmanan Eswaramoorthy (Journal of Chemistry)
Cancer is characterized by abnormal cell differentiation in or on the part of the body. The most commonly used chemotherapeutic drugs are developed to target rapidly dividing cells, such as cancer cells, but they also damage healthy epithelial cells. This has serious consequences for normal cells and become responsible for the development of various disorders. Several strategies for delivering the cytotoxic drugs to cancerous sites that limit systemic toxicity and other adverse effects have recently been evolved. Among them, biomolecule-conjugated metal complexes-based cancer targeting strategies have shown tremendous advantages in cancer therapy. This review focuses on several chemoselective biomolecules-bound metal complexes as prospective cancer therapy-targeted agents. In this review, we presented the details of the various extra- and intracellular targeting mechanisms in cancer therapy. We also addressed the current clinical issues and recent therapeutic strategies in targeted cancer therapy that may pave a way for the future direction of metal complexes-based targeted cancer therapy.